Biology of Albacore tuna (Thunnus alalunga, Bonnaterre 1788) off the South West Coast of South Africa - Norman, Stewart James (Department of Biological Sciences, 2014)
Albacore tuna (Thunnus alalunga) is a highly migratory species found in all of the worlds oceans. The origin of albacore south of Africa is in question. This species constituted 85% of catches of the South African commercial tuna fishing fleet from 2000-2009 and is an important species in supporting a large boat-based recreational fishery. Albacore were sampled at angling competitions, which offer a repeatable and cheap source of tuna, in the Western Cape of South Africa during 2012 and 2013. 119 Samples were used to determine a length-weight relationship and to provide conversion ratios of various body measurements to fork length when total length was not available. Visual examination of testes and ovaries indicated that albacore are not spawning off the coast of South Africa.A comparison between the ease of using sectioned sagittal otoliths and first dorsal spines indicated that otoliths were more precise for estimating the age of albacore. Von Bertalanffy growth parameters were estimated from 51 fish, ranging from 2-9 years old (L∞=1100.07 mm; K=0.238 y-1; t₀=-2.14). Stomach content analysis indicated that the mesopelagic squid Lycoteuthis lorigera is the most important prey item for South African albacore. δ13C and δ15N stable isotope analysis of albacore and yellowfin tuna (T. albacares) muscle tissue showed that they feed on prey that may depend on different primary producers but that the two species of tuna share the same niche in the southern Benguela food web. Trophic levels of 3.8 and 3.76 were assigned to albacore and yellowfin tuna respectively.